Tanshinone I, tanshinone IIA, and cryptotanshinone: key bioactive components modulating vascular smooth muscle cell function - Li, Jixin; Wang, Wenru; Huang, Hongbo; Zhou, Ruiling; Yang, Zhenyu; Cui, Zhijie; Niu, Zelong; Shi, Shengnan; Wang, Peili (Frontiers in Pharmacology, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality among non-communicable diseases worldwide. Vascular smooth muscle cells (VSMCs), as the predominant cellular component of the tunica media, are essential for maintaining vascular homeostasis through phenotype-dependent regulation of vascular tone, blood pressure, and hemodynamics. Under pathological conditions such as hypoxia or inflammation, VSMCs undergo phenotypic switching from a contractile to a synthetic state. This transition is characterized by excessive proliferation, migration, and pro-inflammatory secretion, all of which contribute to the progression of atherosclerosis and restenosis. Tanshinones, bioactive diterpenoid compounds isolated from Salvia miltiorrhiza, exert cardioprotective effects through their anti-inflammatory, antioxidant, and VSMC-modulating activities. Increasing evidence suggests that tanshinones attenuate maladaptive VSMC behaviors by regulating calcium signaling, modulating programmed cell death pathways, and suppressing pro-inflammatory signaling cascades. These actions collectively inhibit phenotypic switching and mitigate vascular remodeling and plaque formation. Despite these advances, a comprehensive understanding of the precise molecular targets and signaling networks of tanshinones in VSMCs is still lacking. This review aims to integrate current evidence to delineate tanshinone-mediated VSMC regulatory mechanisms, provide mechanistic insights, and identify potential therapeutic targets for phenotype-directed interventions in CVDs.